2021
DOI: 10.1093/jjco/hyab081
|View full text |Cite
|
Sign up to set email alerts
|

Smaller decline of renal function after nephroureterectomy predicts poorer prognosis of upper tract urothelial carcinoma: a multicentre retrospective study

Abstract: Purpose Renal function is frequently impaired in the patients with upper tract urothelial carcinoma. We aimed to evaluate the impact of renal function and its change after surgery on survival rates in patients with upper tract urothelial carcinoma after nephroureterectomy. Methods The study cohort comprised 755 patients with upper tract urothelial carcinoma who underwent nephroureterectomy between 1995 and 2016 at nine hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Because RNU results in the loss of a unilateral kidney, impaired renal function is prevalent in patients with UTUC. Using a eGFR cutoff of <60 mL/min/1.73 m 2 (CKD stage ≥3), the rate of patients with postoperative eGFR ≥60 mL/min/1.73 m 2 was 9.0%, which was similar to that reported in previous studies from Japan (9.1%–11.3%), 2,18 but lower than in Western countries (range, 16%–22%, Figure 5). 4–6 The median decline in eGFR after surgery was 25.1%, which was slightly higher reported in previous studies (range, 13.1%–24%) 2,4–6 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Because RNU results in the loss of a unilateral kidney, impaired renal function is prevalent in patients with UTUC. Using a eGFR cutoff of <60 mL/min/1.73 m 2 (CKD stage ≥3), the rate of patients with postoperative eGFR ≥60 mL/min/1.73 m 2 was 9.0%, which was similar to that reported in previous studies from Japan (9.1%–11.3%), 2,18 but lower than in Western countries (range, 16%–22%, Figure 5). 4–6 The median decline in eGFR after surgery was 25.1%, which was slightly higher reported in previous studies (range, 13.1%–24%) 2,4–6 .…”
Section: Discussionsupporting
confidence: 85%
“…Because kidney size is related to a number of glomeruli, body size is a key factor in renal function 19 . The median body mass index in Japanese patients is 22.7 kg/m 2 (IQR: 20.8–24.6 kg/m 2 ) compared with 28.2 kg/m 2 (IQR: 24–32 kg/m 2 ) in Western countries 2,4 . The difference in the prevalence of preoperative hydronephrosis and CKD stage ≥3 compared with Western studies 2,4–6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After RNU for UTUC, patients may require adjuvant chemotherapy for advanced stage or disease progression. Only 50% of patients are still eligible for platinum-based protocols, due postoperative renal function failure [ 8 10 ] which effects oncological outcomes as recently demonstrated [ 5 ]. Early identification of patients at high risk of eGFR reduction after extirpative surgery, for whom adjuvant therapy is no longer feasible, may be addressed by neoadjuvant regimens, resulting in an increase in survival [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…UTUC patients have an increased risk of chronic kidney disease(CKD) because of age, comorbidities, smoking exposure, and potential impairment of contralateral kidney due to diagnostic procedures or contralateral UTUC [ 4 ]. Previous studies showed that CKD may lead to worse overall and cancer-specific survival after treatment for renal cell carcinoma (RCC) as well as UTUC [ 5 , 6 ]. Despite the benefit of adjuvant chemotherapy in prolonging survival [ 7 ] and reducing the risk of disease recurrence in locally advanced UTUC [ 8 ], 50% of patients are not eligible for platinum-based protocols due to postoperative renal failure [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%